POTRET DASAR KEBIJAKAN EKONOMI UTSMANIYAH: SUATU SOROTAN LITERATUR - Sugeng, Anggoro (Journal of Islamic Economics Lariba, 2015)
Economic policy of the state is a process to achieve certain goals implemented by the government of a country. The existence of a country's economic goals, means of support necessary to achieve it. Guidelines and state policy directions can be budget plan, capital improvements formulated by the state for use in the future. In economic studies, economic policy of a country is divided into two parts, namely monetary policy and fiscal policy. This article aims to understand the issues from both the Ottomans basic economic policies, both monetary and fiscal. While the methodology used is to look at the literature of the researchers highlight different perspectives and views, which of all the literature is intended to complement and add to the treasures of knowledge in the basic scope Ottomans policy. As for the results of this study are the determination of money Akce evidence and found that the money was not used during the reign of Ottomans. While the existence of trade relations between the Ottomans and the European economy is a factor increasing Ottomans and a cause of the decline in currency values Akce, Ottomans were in short supply in addition to gold and silver as a money it self. The results of the study of fiscal policy shows that the fiscal deficit is not a political matter but due to a mistake in policy Ottomans empire, either in the form of debt, delivery of various rich region, reduced state revenues, the department 's financial plan swells each year, the lack of audit and account, corruption and differences in the pattern of the budget of the Islamic calendar and the AD were used simultaneously.